Allergenicity of roasted peanuts treated with a non-human digestive protease. (March 2015) - Yu, Jianmei; Hernandez, Michelle; Li, Hao; Goktepe, Ipek; Robinette, Carole; Auerbach, Amy; Peden, David; Ahmedna, Mohamed
Abstract: Peanut allergy is a severe and lifelong type of food allergy triggered by allergenic proteins and peptides in peanuts. This study investigated the effects of ultrasound-assisted alcalase treatment on the concentrations of major allergenic proteins (Ara h 1 and Ara h 2) in roasted peanut kernels and the allergenicity of treated peanut extracts. Peanut kernels were sonicated for 1 h in buffer solution, incubated with different amount of alcalase for various time, then vacuum dried. The variations of Ara h 1 and Ara h 2 contents in soluble and insoluble portions of peanuts treatments were evaluated by sandwich ELISA and SDS-PAGE, respectively. The in vitro IgE-binding capacity of treated peanut extracts was determined by a competitive inhibition ELISA using pooled plasma of 10 peanut allergic patients. Samples with lower in vitro IgE-binding were used for human skin prick tests (SPTs) in peanut allergic individuals. Results indicate that alcalase digestion of sonicated peanuts significantly increased protein solubility while decreasing Ara h 1 and Ara h 2 concentrations in both soluble and insoluble portions of peanuts relative to untreated peanuts. The maximum reductions of Ara h 1 and Ara h 2 levels were obtained following 3 hour digestion with alcalase at concentrations of 4.54 and 6.05 U/100 g. Samples obtained under these conditions showed the lowest in vitro IgE-binding and caused the least allergic response in human SPTs. The current study suggests that the allergenic potential of peanuts could be reduced by postharvest processing such as ultrasound-assisted enzymatic treatment of peanuts kernels. Highlights: Peanut allergy is a severe food allergy and difficult to outgrow. Peanut allergy is caused by allergenic proteins. Alcalase effectively reduced the allergenic protein content in this study. IgE-binding tests showed reduced in vitro allergenicity of alcalase treated peanuts. The in vivo skin prick test results agreed well with that of in vitro tests.